Laboratory Diagnosis of Significant Bacterial Organisms in Mixed Sexually Transmitted Infections - Shamala , Moodley; Dharshni , Pillay; Mohini , Pillay (Innovations in Microbiology and Biotechnology Vol. 8, 2022)
Sexually Transmitted Infections (STIs) are transmitted sexually from individual to individual via body fluids, blood, semen, or vaginal fluids. In this review the epidemiology, diagnosis and management of Chlamydia trachomatis, Neisseria gonorrhoeae, syphilis and, Trichomonas vaginalis are discussed. When STIs are left undiagnosed or not treated promptly, a sequelae of health complications can occur which includes salpingitis, pelvic inflammatory disease, infertility and ectopic pregnancies in women and sterility in men. Studies have observed that higher rates of STIs occur amongst individuals 25 years and younger. Globally, it has been reported that there is a definitive increase in STIs. The suggestion is that the increase is indicative of an epidemic, with profound consequences on health care systems. Therefore, diagnosis of the STI infections is of paramount importance when screening both symptomatic and asymptomatic individuals. These tests can range from the traditional to the more current assays. The choice of assays is dependent on the availability of resources. Test methods used should meet certain criteria such as accuracy, sensitivity, specificity, and affordability. These techniques are also, assessed on the rapidity, reliability, cost effectiveness and ease on collection of specimens. Isolation of the causative organism/s is undertaken firstly by direct detection of the organism, followed by microscopic identification, using appropriate staining techniques. The process may be concluded with culture, serology, or nucleic acid detection (using amplified or non-amplified nucleic acid tests). Diagnostic technologies have various advantages however, these are also inundated with challenges. Even though automation of methods results in a rapid turnover time and increase in accuracy, there are certain limitations which needs to be addressed. Molecular techniques are increasingly used, to improve patient care, in most developed countries. In less developed countries the assessment of choice is usually culture and serological tests.